Intermittent Preventive Treatment The challenge of implementation - Bell, Allison (مجلة الجزيرة للعلوم الصحية; مجلد 1 عدد 1 (2004), 2004)
The Direct consequences of malaria during pregnancy are more prevalent in unstable transmission areas. In those areas pregnant women have little or on immunity. In those women malaria causes hyperpyrexia, hypoglycaemia, severe haemolytic anaemia, cerebral malaria and pulmonary oedema and maternal death if not treated. (Looareesuwan et al 1985). Fever in pregnancy may bring about abortion or intrauterine foetal death. The average malaria in pregnancy case fatality varies from 1% in low endemic areas to 13.1% in epidemics (Brabin 7003).           The indirect consequences of malaria during pregnancy are more prevalent in stable transmission areas. In such settings the main maternal effect is anaemia, which is frequently severe and a risk factor for maternal death. The contribution of malaria to maternal mortality is estimated as 0.5-23% of hospital based deaths and 2.9-17.6% of community based maternal deaths. The second important effect of malaria in pregnancy in areas of stable transmission is low birth weight (LBW). 20% of children born in Malawi are LBW; malaria was most important contributory factor to LBW (verhoef et al 1988). LBW in Malawi contributed to 80% of all neonatal deaths and 38% of infant mortality (MC Dermott et al 1996). LBW is the single biggest risk factor for neonatal mortality and major contributor to infant mortality (Mc Cormick 1985).